AMP-activated protein kinase, super metabolic regulator. (1st February 2003) - Kemp, B.E.; Stapleton, D.; Campbell, D.J.; Chen, Z.-P.; Murthy, S.; Walter, M.; Gupta, A.; Adams, J.J.; Katsis, F.; van Denderen, B.; Jennings, I.G.; Iseli, T.; et al.
Abstract : The AMP-activated protein kinase (AMPK) is a metabolic-stress-sensing protein kinase that regulates metabolism in response to energy demand and supply by directly phosphorylating rate-limiting enzymes in metabolic pathways as well as controlling gene expression.